(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
Teaching learners with hearing impairments in inclusive learning environment require identification and elimination of learning barriers. The current education policy in Zambian, ‘Educating our future’ of 1996 stresses the need to teach learners with disabilities inclusively. Effective inclusion of learners with hearing impairments entails identification of their learning barriers and making the learning environment accommodative. This paper is a literature review of some barriers that learners with hearing impairments experience in learning in inclusive learning environments and some accommodative measures to consider when teaching learners with hearing impairments. In this article we shall first explore the concept of hearing impairment and inclusive education from a historical perspective and thereafter explore the barriers that learners with hearing impairments experience in learning and review some accommodative measures for learners with hearing impairments in inclusive environments. Keywords: Barriers. Deaf. Hearing Impairment. Inclusive Education. Learners